Upaya Meningkatkan Daya Ingat dan Hasil Belajar Siswa melalui Penggunaan Media Permainan Memory Game dalam Pembelajaran Pendidikan Pancasila Materi Sejarah Perumusan Pancasila Kelas IV SD - Alifia Yoranika Ramadhani; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila Education plays a crucial role in shaping national character and strengthening the national identity of students from an early age. However, learning activities in elementary schools remain largely rote-based and monotonous, making it difficult for students to understand and remember important events and figures in the history of Pancasila formulation. This study aims to improve students’ memory retention and learning outcomes through the implementation of the Memory Game as an instructional medium in the topic History of Pancasila Formulation for fourth-grade students. The research employs a Classroom Action Research (CAR) method using a mixed-methods approach, combining both qualitative and quantitative data. Data collection techniques include observation, teacher interviews, documentation, and learning achievement tests (pre-test and post-test). The results of the study show that the use of the Memory Game increased the students’ average scores from 42.6 to 84.4, with 88.9% of students achieving mastery learning. Students appeared more enthusiastic, active, and capable of recalling the names and roles of the Panitia Sembilan (Committee of Nine) members more easily. These findings demonstrate that game-based learning is effective in strengthening visual memory and enhancing students’ learning motivation. The study reinforces the principles of active learning and constructivism, while practically offering an innovative media alternative aligned with the Merdeka Curriculum framework. It is recommended that future research develop an interactive digital version of the Memory Game to enable broader and more sustainable application.